Biaxially oriented polyester film for dry film resist support
By controlling the dimensional change rate of the biaxially oriented polyester film at high temperature and setting up a multi-layer stacked structure, the problem of insufficient adaptability in high-temperature lamination processing is solved, and the effect of excellent resist optical characteristics and film productivity is achieved.
Patent Information
- Application Number
- CN202380055747.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-07-24
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to improve the adaptability of the biaxially oriented polyester film in high-temperature lamination processing, while maintaining excellent optical properties of the resist and film productivity.
By controlling the film size change rate when the temperature rises from 90°C to 130°C in the biaxially oriented polyester film, the thickness and surface roughness of the film are optimized in the width and length directions.
It achieves excellent adaptability for high-temperature lamination processing, maintains excellent optical characteristics of resist and film productivity, and avoids defects and reduced productivity in lamination processing.
Smart Images

Figure BDA0005254091310000141 
Figure BDA0005254091310000231 
Figure BDA0005254091310000251
Abstract
Description
Technical Field
[0001] The present invention relates to a biaxially oriented polyester film for a dry film resist support which improves high temperature lamination processability in a dry film resist processing step by controlling the thermal dimensional change rate at a specific temperature and which is excellent in resist optical properties and film productivity. Background Art
[0002] Polyester resins are used in various industrial fields because of their good processability. In addition, products processed into film-like products (biaxially oriented polyester films) of these polyester resins play an important role in current life such as industrial use, optical product use, packaging use, and magnetic recording tape use.
[0003] In recent years, miniaturization and high integration have been progressing in electronic information equipment, and with this, the miniaturization of the wiring of electronic information equipment has also been progressing. In the production of the fine wiring of these electronic information devices, a dry film resist construction method is often used, in which a material having a transparent film as a support and a photocurable resin layer (resist layer) provided on the surface is closely attached to a substrate (copper foil substrate) bonded with a thin film of copper, and the wiring shape is depicted using a photoresist technique together with the film, and the film is washed after peeling to form the copper wiring. For the next generation of products, very fine processing with a wiring width of 2 to 5 μm is required.
[0004] Generally speaking, after the biaxially oriented polyester film is made into a film in the manufacturing process, it is wound into a roll. At this time, if the film surface is too smooth, the films are closely attached to each other, so the winding property of the film deteriorates. Therefore, in order to ensure the winding property of the film, it is known that by adding / containing particles in the film, the film surface is made rough to a certain extent (forming projections on the film surface). By reducing the amount of the added particles, or reducing the particle size of the added particles, the optical properties of the film that contributes to the resist wiring depiction can be improved. On the other hand, due to the reduction in the number and height of the projections present on the film surface, surface scratches and poor winding occur in the polyester film manufacturing process, thereby reducing productivity, so the optical properties of the resists of these films and productivity become a problem.
[0005] In addition, the conditions of the lamination process in the dry film resist are generally based on the thermal properties of the resist layer and the combination with the copper foil substrate used. In general, a rubber roller heated to 90°C or above is used to pressurize it to make it close, but in recent years, the demand for processing under high temperature conditions up to 120-130°C has increased. Generally speaking, if the polyester film is heated at a temperature above the glass transition temperature, the film shrinks thermally, so during the lamination process, there is a difference in the thermal dimensional change rate in the width direction of the resist layer, so that due to the poor adhesion between the copper foil substrate and the resist layer, bubbles are bitten (lamination gaps), resulting in defects in the subsequent photoresist process. Therefore, it is important to control the thermal dimensional change rate of the biaxially oriented polyester film in the process of being heated from 90°C to around 130°C (heating process) to improve the lamination processability.
[0006] As a method for controlling the thermal dimensional change of a biaxially oriented polyester film, a technology for controlling the dimensional change before and after the heat treatment by performing a high-temperature heat treatment in the film forming process is described in Patent Documents 1 to 3, and a technology for similarly controlling the thermal dimensional change by using a heat-resistant polyester resin is described in Patent Document 4.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-160240
[0010] Patent Document 2: Japanese Patent Application Publication No. 2021-054069
[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 10-24665
[0012] Patent Document 4: Japanese Patent Application Publication No. 2015-178623 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, the temperature of the relaxation treatment required to control the heat treatment temperature and the dimensional change rate in Patent Documents 1 and 2 is low, and it is difficult to control the thermal dimensional change rate at the target temperature of 90°C to 130°C. In addition, Patent Document 3 achieves the control of the thermal dimensional change rate with a 4.5 μm film by combining high area ratio stretching and re-stretching. However, due to the thin film thickness, the film has no rigidity (stiffness), and wrinkles are easily introduced during lamination due to the slight shaking of the roll movement. In addition, if tension is applied to the film to eliminate wrinkles, the film will rupture, so the lamination process adaptability is significantly reduced.
[0015] In Patent Document 4, since a heat-resistant polyester resin is used as a copolymer component, the thermal properties can be controlled. On the other hand, since the surface roughness increases due to the copolymer component and the optical properties in the film become uneven, the optical properties are significantly reduced when used as a film for a dry film resist support, which is not preferred.
[0016] An object of the present invention is to provide a biaxially oriented polyester film for a dry film resist support which has excellent suitability for high temperature lamination processing and excellent resist optical properties and film productivity.
[0017] Means for solving problems
[0018] [I] A biaxially oriented polyester film for a dry film resist support, wherein the film dimensional change rate when the film temperature is raised from 90°C to 130°C is denoted as ΔL 90-130℃ (ppm / °C), ΔL in at least one direction of the width direction (TD direction) and the length direction (MD direction) 90-130℃ The value is -50 or more and 150 or less, and the total film thickness T (μm) is 11 or more and 50 or less.
[0019] [II] The biaxially oriented polyester film for a dry film resist support according to [I], wherein the film dimensional change rate when the film temperature is increased from 90° C. to 130° C. is denoted as ΔL 90-130℃ (ppm / °C), ΔL in at least one direction of the width direction (TD direction) and the length direction (MD direction) 90-130℃ The total film thickness T (μm) is 20 to 150 μm, and the total film thickness T (μm) is 11 to 50 μm.
[0020] [III] The biaxially oriented polyester film for a dry film resist support according to [I] or [II], wherein the ΔL 90-130℃ (ppm / °C) in the direction of -50 or more and 150 or less, the dimensional change rate ΔL when the film temperature is increased from 110°C to 130°C 110-130℃ (ppm / °C) is 0 or more.
[0021] [IV] The biaxially oriented polyester film for a dry film resist support according to [I] or [II], wherein the film is oriented in a direction relative to the above ΔL 90-130℃ The dimensional change rate ΔL when the temperature is increased from 90°C to 130°C in the direction where (ppm / °C) is -50 or more and 150 or less, which is the perpendicular direction in the plane. 90-130 °C (ppm / °C) is -200 or more and 0 or less.
[0022] [V] The biaxially oriented polyester film for a dry film resist support according to [I] or [II], wherein the ΔL 90-130℃(ppm / °C) in the direction where the dimensional change rate ΔL when the film temperature is increased from 90°C to 110°C is -50 or more and 150 or less. 90-110℃ (ppm / °C) is 0 or more.
[0023] [VI] The biaxially oriented polyester film for a dry film resist support according to [I] or [II], wherein the root mean square roughness Sq (nm) of at least one surface is 0.8 or more and less than 3.0.
[0024] [VII] The biaxially oriented polyester film for a dry film resist support according to [I] or [II], comprising a P1 layer as at least one outermost layer, wherein the P1 layer is a layer containing particles having an average primary particle size of 70 nm to 200 nm.
[0025] [VIII] The biaxially oriented polyester film for a dry film resist support according to [VII], wherein the thickness of the P1 layer is set to T P1 (μm) T P1 It is 0.03 or more and 0.35 or less.
[0026] [IX] The biaxially oriented polyester film for a dry film resist support according to [VII], wherein the root mean square roughness of the surface of the P1 layer is set to Sq P1 (nm) in the case of Sq P1 (nm) is 0.8 or more and less than 3.0.
[0027] [X] The biaxially oriented polyester film for a dry film resist support according to [VII], wherein the outermost layer (P2 layer) on the opposite side to the P1 layer satisfies the following (1) and (2).
[0028] (1) Does not contain particles with an average primary particle size of 200 nm or more
[0029] (2) The surface has protrusions, and the number of protrusions with a height of 10 nm or more is N. 10nm (pcs / mm 2 ) 10nm 600 or more and 12000 or less
[0030] [XI] The biaxially oriented polyester film for a dry film resist support according to [X], further comprising a P3 layer between the P1 layer and the P2 layer, wherein the P3 layer has a lower particle concentration than the P1 layer, or contains no particles.
[0031] [XII] The biaxially oriented polyester film for a dry film resist support according to [VII], wherein the number of coarse particles with a major diameter of 2.0 μm or more existing in a region 3 μm away from the P1 layer in the thickness direction as observed by an optical microscope is set as NP1 (pcs / 8.25mm), N P1 Below 20.
[0032] Effects of the Invention
[0033] The present invention provides a biaxially oriented polyester film for a dry film resist support, which is excellent in suitability for high temperature lamination processing and excellent in resist optical properties and film productivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a conceptual diagram showing a surface having protrusions (P2 layer surface) measured using a scanning white interference microscope.
[0035] Figure 2 The two-layer structure diagram of the biaxially oriented polyester film of the present invention is shown in FIG.
[0036] Figure 3 The three-layer structure of the biaxially oriented polyester film of the present invention is shown in FIG.
[0037] Figure 4 The four-layer structure of the biaxially oriented polyester film of the present invention is shown in FIG. DETAILED DESCRIPTION
[0038] Hereinafter, the present invention will be described in detail.
[0039] The present invention relates to biaxially oriented polyester films.
[0040] The present invention is a biaxially oriented polyester film for a dry film resist support, wherein the film dimensional change rate when the film temperature is raised from 90°C to 130°C is denoted as ΔL 90-130℃ (ppm / °C), ΔL in at least one direction of the width direction (TD direction) and the length direction (MD direction) 90-130℃ The value is -50 or more and 150 or less, and the total film thickness T (μm) is 11 or more and 50 or less.
[0041] (Polyester resin)
[0042] The biaxially oriented polyester film for a dry film resist support of the present invention preferably has a structure containing a polyester resin as a main component.
[0043] The biaxially oriented polyester film in the present invention refers to a film containing a polyester resin as a main component. The main component here refers to a component contained in an amount exceeding 50% by mass in 100% by mass of all components of the film.
[0044] In addition, the polyester resin in the present invention is obtained by polycondensation of a dicarboxylic acid constituent component and a diol constituent component. It should be noted that in the present specification, the constituent component refers to the smallest unit that can be obtained by hydrolyzing a polyester.
[0045] Examples of dicarboxylic acid components constituting such polyesters include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 4,4′-diphenyl dicarboxylic acid, and 4,4′-diphenyl ether dicarboxylic acid, or ester derivatives thereof.
[0046] Examples of the diol constituent components constituting such polyesters include aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,2-butylene glycol, and 1,3-butylene glycol; alicyclic diols such as cyclohexanedimethanol and spiroglycol; and products obtained by linking a plurality of these diols.
[0047] As the polyester resin used in the present invention, from the viewpoint of mechanical properties and transparency, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene 2,6-naphthalate (PEN), and a material obtained by copolymerizing isophthalic acid or naphthalene dicarboxylic acid with a part of the dicarboxylic acid component of PET, and a polyester obtained by copolymerizing cyclohexanedimethanol, spiroglycol, or diethylene glycol with a part of the diol component of PET are preferably used. Among them, polyethylene terephthalate is particularly preferred.
[0048] (Biaxially oriented polyester film)
[0049] The biaxially oriented polyester film for the dry film resist support of the present invention is biaxially oriented, so that the mechanical strength of the film is improved and wrinkles are not easily introduced, and the winding property can be improved. In addition, in the stretching process, uniform tensile stress is applied so that the smoothness of the surface can be uniform in the entire area of the film. Here, the so-called biaxial orientation refers to a pattern showing biaxial orientation in wide-angle X-ray diffraction. Generally speaking, the polyester film can be obtained by stretching the thermoplastic resin sheet in an unstretched state along the length direction and the width direction of the sheet, and then performing heat treatment and relaxation treatment to complete the crystal orientation. It will be described in detail later.
[0050] In the biaxially oriented polyester film for a dry film resist support of the present invention, when the intrinsic viscosity (IV) of the entire film is IV (dl / g), IV (dl / g) is preferably 0.55 or more and 0.80 or less. By making IV (dl / g) 0.55 or less, the mechanical properties in the stretching film-forming process are improved, and the reduction in the film-forming yield due to film rupture can be suppressed. In addition, by making IV 0.8 or less, extrusion defects in the melt extrusion process can be suppressed.
[0051] The biaxially oriented polyester film for a dry film resist support of the present invention preferably has a laminated structure of at least two layers such as a P1 layer / P2 layer including a moving surface layer (P1 layer) containing particles and a layer (P2 layer) having protrusions.
[0052] From the viewpoint of improving the optical properties of the biaxially oriented polyester film of the present invention, it is more preferred to have a laminated structure of at least three layers, such as a laminated structure of different types of three layers consisting of P1 layer / P3 layer / P2 layer, with an intermediate layer (P3 layer) containing no particles and recycled raw materials between the above-mentioned P1 layer and the above-mentioned P2 layer. In addition, from the viewpoint of controlling the surface roughness of the P1 layer, the P2 layer or the P4 layer containing particles in a range that has no effect on the thermal dimensional change rate and optical properties of the present invention can be made the base layer of the P1 layer, and a four-layer laminated structure of P1 layer / P2 layer / P3 layer / P2 layer, or P1 layer / P4 layer / P3 layer / P2 layer is also a preferred structure. Details will be described later.
[0053] There are no particular restrictions on the method of laminating the P1 layer, P2 layer and P3 layer composed of polyester resin respectively, and the coextrusion method described below, a method of feeding other resin layer raw materials into an extruder for melt extrusion and laminating them on a film in the middle of film making (melt lamination method), a method of laminating the films after film making with each other via an adhesive layer, and a method of setting by coating during or after the film making process (online coating method, offline coating method), etc., can be used. Among them, the coextrusion method that can simultaneously perform protrusion formation and lamination using the above-mentioned treatment is preferably used.
[0054] When the total thickness of the biaxially oriented polyester film for the dry film resist support of the present invention is set to T (μm), T is preferably 11 or more and 50 or less. By setting the total film thickness T (μm) to 11 or more, the occurrence of winding wrinkles during the film winding during the production of the biaxially oriented polyester film due to insufficient rigidity of the film can be suppressed, and when used as a film for a dry film resist support, the occurrence of wrinkles in the lamination process can be suppressed, and the occurrence of film cracks in the resist layer coating process, high-temperature lamination process, and heat treatment process can be suppressed. In addition, by setting the total film thickness T (μm) to 50 or less, the occurrence of light scattering of the photoresist due to foreign matter inside the film generated by the polyester resin raw material can be suppressed, and the occurrence of pinhole defects in the resist wiring can be suppressed, and the film rigidity of the biaxially oriented polyester film is prevented from being excessively increased, so that the processability can be improved. As the lower limit of the total film thickness T (μm), it is more preferably 15 or more. The upper limit of the total film thickness T (μm) is more preferably 35 or less, and further preferably 25 or less.
[0055] (Thermal Dimensional Properties of Biaxially Oriented Polyester Film)
[0056] The biaxially oriented polyester film for a dry film resist support of the present invention needs to have a film dimensional change rate when the film temperature is raised from 90° C. to 130° C. as ΔL. 90-130℃ (ppm / °C), ΔL in at least one direction of the width direction (TD direction) and the length direction (MD direction) 90-130℃ It is -50 or more and 150 or less.
[0057] The film size change rate ΔL when the film temperature is raised from 90°C to 130°C is 90-130℃ (ppm / ℃) is a value obtained by measuring by thermomechanical analysis (TMA) described later. It is a value indicating the dimensional change rate of the biaxially oriented polyester film for the dry film resist support of the present invention when heated by a high-temperature lamination roller in the lamination process, and is a value indicating expansion if the value is positive and contraction if the value is negative. 90-130℃ (ppm / ℃) is -50 or more, so that the heat shrinkage can be reduced to an appropriate range. Therefore, in the present invention, the following phenomenon can be suppressed: in the high-temperature lamination process, the biaxially oriented polyester film shrinks more than the resist layer, so that curling sometimes occurs on the biaxially oriented polyester side, the copper foil substrate and the resist layer that are closely bonded are peeled off, and floating occurs between the copper foil substrate and the resist layer. 90-130℃ The lower limit of (ppm / °C) is more preferably 0 or more, and further preferably 20 or more. 90-130℃ (ppm / °C) is 150 or less, so that thermal expansion can be reduced to an appropriate range. In the high-temperature lamination process, the biaxially oriented polyester film has expanded more than the resist layer in the past, so that the resist layer bonded to the biaxially oriented polyester film is sometimes excessively stretched, resulting in tiny defects in the resist layer, which is the starting point for floating between the copper foil substrate and the resist layer, but this phenomenon can be suppressed in the present invention. As the above-mentioned ΔL 90-130℃ The upper limit of (ppm / °C) is more preferably 85 or less.
[0058] Regarding the above ΔL 90-130℃ A method in which (ppm / °C) is above -50 and below 150 can be achieved by subjecting the biaxially stretched film to a heat treatment at a temperature above a certain temperature and a relaxation treatment at a temperature above a certain temperature in the transverse stretching step during the biaxial stretching of the polyester film described later in the film making, the heat treatment, and the relaxation treatment in the width direction.
[0059] Specifically, it is preferred that the biaxially oriented polyester film is subjected to heat treatment at a temperature of 221°C to 240°C, and a relaxation treatment is performed at a ratio of 1% to 4% in the width direction at the same temperature as the heat treatment temperature. By relaxing the excessive orientation stress remaining in the polyester resin molecular chain in the biaxially oriented film due to biaxial stretching while shrinking slightly in the width direction, it is possible to improve the thermal dimensional stability while maintaining the planarity. By making the ratio of the relaxation treatment in the width direction 1% or more, the above-mentioned orientation stress relaxation effect is obtained, and by making the ratio of the relaxation treatment in the width direction 4% or less, it is possible to suppress the introduction of periodic wrinkles called corrugation wrinkles to the biaxially oriented polyester film due to rapid heat shrinkage, thereby reducing the quality. A further preferred range of the heat treatment temperature is 225°C to 240°C, and most preferably 230°C to 240°C. In addition, as a preferred range of the ratio of the relaxation treatment (relax treatment) in the width direction performed at the heat treatment temperature, the lower limit is more preferably 1.5% or more, and the upper limit is more preferably 2.5% or less.
[0060] In the above ΔL 90-130℃ In the direction where (ppm / °C) satisfies -50 or more and 150 or less, in order to make the above ΔL 90-130℃ (ppm / °C) is a more preferred range, and it is preferred that after the above-mentioned relaxation treatment in the width direction, the relaxation treatment in the width direction is carried out at a temperature of 90°C to 150°C corresponding to the lamination processing temperature range at a ratio of 0.5% to 3%. This is because the polyester resin molecular chains in the film form a stable structure at the lamination processing temperature by performing the relaxation treatment in the width direction at the above temperature.
[0061] In addition, as a method of performing the relaxation treatment at a temperature of 90°C to 150°C, it is further preferred to perform the relaxation treatment in the width direction two or more times in two different temperature regions, and it is most preferred to perform the relaxation treatment in the width direction at a temperature of 115°C to 150°C at a ratio of 0.5% to 2.0%, and then perform the relaxation treatment in the width direction at a temperature of 90°C to less than 115°C at a ratio of 0.3% to 2.0%. The reason is that by using the preferred relaxation treatment method, the film dimensional change rate ΔL when the temperature is increased from 90°C to 110°C described later can be reduced. 90-110℃ (ppm / °C), and the film size change rate ΔL when the temperature is increased from 110°C to 130°C 110-130℃ (ppm / ℃) increases, and with this, the above ΔL 90-130℃The value of (ppm / °C) increases. As the ratio of the relaxation treatment (relax treatment) in the width direction performed at a temperature of 115°C to 150°C, the lower limit is more preferably 1.0% or more, and the upper limit is more preferably 1.8% or less. In addition, as the preferred ratio of the relaxation treatment (relax treatment) in the width direction performed at a temperature of 90°C to less than 115°C, the lower limit is more preferably 0.5% or more, the upper limit is more preferably 1.5% or less, and further preferably 0.8% or less.
[0062] Furthermore, the total relaxation treatment ratio at each temperature after the heat treatment is preferably 5% or less. By making the total relaxation treatment ratio 5% or less, it is possible to suppress the deterioration of quality due to the introduction of periodic wrinkles called moire wrinkles caused by heat shrinkage in a state where the biaxially oriented polyester film is excessively relaxed. More preferably, the total relaxation treatment ratio is 4.5% or less.
[0063] In order to match the thermal dimensional change rate of the resist layer, when the biaxially oriented polyester film for a dry film resist support of the present invention is used for high temperature lamination processing, the above ΔL is set to 90-130℃ It is a more preferred embodiment that the direction in which the (ppm / °C) is -50 or more and 150 or less is the width direction (TD direction) of the roll during lamination.
[0064] The biaxially oriented polyester film for a dry film resist support of the present invention is preferably 90-130℃ The film dimensional change rate ΔL when the film temperature is increased from 90°C to 130°C is in the direction perpendicular to the plane (ppm / °C) of -50 or more and 150 or less. 90-130℃ (ppm / °C) is -200 or more and 0 or less. 90-130℃ (ppm / °C) ΔL in the direction of -50 or more and 150 or less, which is the perpendicular direction in the plane 90-130℃ (ppm / °C) of -200 or more and 0 or less indicates that the film shrinks in the temperature range of 90°C or more and 130°C or less. 90-130℃ (ppm / °C) ΔL in the direction of -50 or more and 150 or less, which is the perpendicular direction in the plane 90-130℃ (ppm / °C) is -200 or more and 0 or less, thereby applying appropriate tension to the unwinding direction of the film that is unwound from the roll due to heat shrinkage during lamination, thereby suppressing the generation of wrinkles. Therefore, when the biaxially oriented polyester film for the dry film resist support of the present invention is used for high-temperature lamination, it is preferred that the direction perpendicular to the above direction in the plane is the unwinding direction. As the above ΔL 90-130℃(ppm / °C) ΔL in the direction of -50 or more and 150 or less, which is the perpendicular direction in the plane 90-130℃ The lower limit of (ppm / °C) is more preferably -150 or more.
[0065] As the film dimensional change rate ΔL in the direction perpendicular to the above-mentioned direction in the plane when the film temperature is increased from 90° C. to 130° C. 90-130℃ The method of controlling the (ppm / °C) within the preferred range can be achieved by performing the above-mentioned heat treatment / relaxation treatment and stretching in the film forming step described later at a stretching ratio of 3.0 to 4.8 times in the longitudinal direction. A more preferred range is 3.5 to 4.8 times.
[0066] The biaxially oriented polyester film for the dry film resist support of the present invention preferably has a ΔL 90-130℃ (ppm / °C) The film dimensional change rate ΔL when the film temperature is increased from 90°C to 110°C in the direction of -50 to 150 90-110℃ (ppm / °C) is 0 or more. 90-110℃ (ppm / °C) is 0 or more, so that when the film is laminated at a temperature of 90°C to 110°C, the difference in dimensional change rate with the resist layer caused by film expansion can be suppressed, thereby assisting the propagation of stress in the width direction when applying pressure using a high-temperature processing roller. 90-110℃ A more preferred range of (ppm / °C) is 30 or more, and more preferably 70 or more. In addition, the upper limit is more preferably 150 or less, and more preferably 120 or less, so that the biaxially oriented polyester film can be prevented from swelling more than the resist layer during the lamination process, thereby preventing the copper foil substrate and the resist layer from floating.
[0067] The biaxially oriented polyester film for a dry film resist support of the present invention preferably has a film dimensional change rate ΔL in the above direction when the film temperature is increased from 110° C. to 130° C. 110-130℃ (ppm / °C) is 0 or more. 110-130℃ (ppm / °C) is 0 or more, so that when the film is laminated at a temperature of 110°C to 130°C, the difference in dimensional change rate with the resist layer caused by film expansion can be suppressed, which is preferred. In addition, this can assist the propagation of stress in the width direction when applying pressure using a high-temperature processing roller, which is preferred. As the above ΔL 110-130℃The preferred range of (ppm / °C) is 10 or more, more preferably 20 or more. The upper limit is more preferably 250 or less, more preferably 100 or less, so that the biaxially oriented polyester film can be prevented from expanding more than the resist layer during the lamination process, thereby preventing the copper foil substrate and the resist layer from floating.
[0068] It is preferred that the root mean square roughness Sq (nm) of at least one side of the biaxially oriented polyester film for a dry film resist support of the present invention is 0.8 or more and less than 3.0. The root mean square roughness (Sq) is a value of average roughness that estimates the influence of high protrusions and deep valleys more than the arithmetic mean roughness (Sa) generally used as the surface roughness, and is a value that reflects the amount of coarse protrusions and concave defects generated at a low probability on the surface, and is a useful value for estimating the optical properties of the resist required for the film for a dry film resist support and the mobility of the film. The root mean square roughness is a value measured by the scanning white interference microscope (VertScan) according to the method described below, based on ISO 25178 solved by the software attached to the scanning white interference microscope, and measured by the measurement method described below.
[0069] When the root mean square roughness Sq (nm) of at least one side surface is 0.8 or more and less than 3.0, when the biaxially oriented polyester film of the present invention is used as a dry film resist support, the side of the surface is the opposite side to the surface where the resist layer is set, and generally speaking, it can be configured and used as a surface (hereinafter sometimes referred to as a moving surface) for irradiating ultraviolet light (hereinafter sometimes referred to as resist light) with a wavelength of 365nm used for resist processing. When the root mean square roughness Sq (nm) is 0.8 or more, the friction between the film surface and the conveyor roller increases in the film manufacturing process and the dry film resist processing process, thereby preventing the film surface from being scratched. In addition, when the root mean square roughness Sq (nm) is less than 3.0, the ultraviolet light used for resist processing in the photoresist process can be prevented from scattering on the film surface, thereby preventing defects in resist wiring. As the lower limit value of the root mean square roughness Sq (nm), it is more preferably 2.0 or more. Furthermore, the upper limit of the root mean square roughness Sq (nm) is more preferably 2.9 or less.
[0070] When the root mean square roughness Sq (nm) of both side surfaces of the biaxially oriented polyester film for the dry film resist support of the present invention satisfies 0.8 or more and less than 3.0, either surface can be set as the moving surface, but it is preferred to set the layer containing particles with a larger average primary particle size as the moving surface from the viewpoint of suppressing the influence of light scattering of the resist light caused by the particles contained therein from being directly propagated to the resist layer.
[0071] (Moving surface layer containing particles: P1 layer)
[0072] The biaxially oriented polyester film for dry film resist support of the present invention preferably has a layer (P1 layer) containing particles having an average primary particle size of 70 nm or more and 200 nm or less. By containing particles having an average primary particle size of 200 nm or less, light scattering when resist light passes through the P1 layer can be suppressed, thereby suppressing the generation of defects in resist wiring. In addition, by containing particles having 70 nm or more in the P1 layer, the mobility of the film during film formation can be improved by making the surface rough. As a further preferred embodiment of the biaxially oriented polyester film for dry film resist support of the present invention, it has a layer (P1 layer) containing particles having an average primary particle size of 70 nm or more and 150 nm or less.
[0073] From the viewpoint of achieving both mobility during film formation and resist optical properties, it is more preferable that the P1 layer is disposed on the side of the mobility surface opposite to the surface on which the resist layer is provided.
[0074] Furthermore, from the viewpoint of suppressing light scattering of resist light, the P1 layer more preferably does not contain particles having an average primary particle size exceeding 200 nm.
[0075] In order to improve the mobility of the film and suppress damage to the surface of the P1 layer, the P1 layer may contain particles having an average primary particle size of less than 70 nm in addition to the particles having an average primary particle size of 70 nm to 200 nm.
[0076] As the particles contained in the P1 layer, either inorganic particles or organic particles may be used, or two or more types of particles may be used in combination.
[0077] As inorganic particles that can be used, for example, calcium carbonate, magnesium carbonate, zinc carbonate, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, zinc sulfide, calcium phosphate, aluminum oxide (α aluminum oxide, β aluminum oxide, γ aluminum oxide, δ aluminum oxide), mica, mica, titanium mica, zeolite, talc, clay, kaolin, lithium fluoride, calcium fluoride, montmorillonite, zirconium oxide, silicon dioxide (wet silicon dioxide, dry silicon dioxide, colloidal silicon dioxide), etc. can be cited. As organic particles, examples can be given, such as organic particles, core-shell organic particles, etc., with acrylic resins, styrene resins, silicone resins, polyimide resins, etc. as constituent components. Among them, for inorganic particles, aluminum oxide or silicon dioxide is preferred from the viewpoint of matching the refractive index with the biaxially oriented polyester film and suppressing the influence on the optical properties of the resist to the minimum. In addition, for organic particles, styrene resins are preferred because their refractive index is close to that of the biaxially oriented polyester film for the same reason.
[0078] In the biaxially oriented polyester film for a dry film resist support of the present invention, the thickness of the P1 layer is defined as TP1 (μm) is preferred P1 (μm) is 0.03 or more and 0.35 or less. P1 (μm) is 0.35 or less, thereby suppressing the light scattering of the resist light caused by the particles contained in the P1 layer, suppressing the pinhole defects during the formation of the resist wiring, and furthermore, by making T P1 (μm) is 0.03 or more, so that particles contained in the P1 layer can be prevented from falling off during film movement. P1 A more preferred range of the upper limit value (μm) is 0.30 or less, and most preferably 0.25 or less.
[0079] The root mean square roughness Sq of the surface of the P1 layer in the biaxially oriented polyester film for a dry film resist support of the present invention is P1 (nm) is 0.8 or more and less than 3.0 because the P1 layer is used as the moving surface to suppress the light scattering of the resist light caused by the particles in the layer. P1 (nm) is 0.8 or more, thereby preventing the surface scratches caused by the friction between the P1 layer surface and the conveyor rollers in the film manufacturing process and the dry film resist processing process. P1 (nm) is less than 3.0, which can inhibit the ultraviolet light used for resist processing in the photoresist process from scattering on the film surface and inhibit the deformation of the wiring shape of the resist wiring. The root mean square roughness Sq of the P1 layer surface is P1 The lower limit of the roughness (nm) is more preferably 2.0 or more. P1 The upper limit of (nm) is more preferably 2.9 or less.
[0080] (Smooth surface layer with protrusions: P2 layer)
[0081] The biaxially oriented polyester film for a dry film resist support of the present invention preferably has a P2 layer satisfying the following (1) and (2) on the opposite surface to the P1 layer.
[0082] (1) Does not contain particles with an average primary particle size of 200 nm or more
[0083] (2) The surface has protrusions, and the number of protrusions with a height of 10 nm or more is N. 10nm (pcs / mm 2 ) 10nm 600 or more and 12000 or less
[0084] By not containing particles with an average primary particle size of 200 nm or more in the above-mentioned P2 layer of the present invention, it is possible to suppress the formation of sudden coarse protrusions on the surface of the P2 layer and the generation of resist layer defects due to the transfer of the concave-convex shape of the surface of the P2 layer when the resist layer is provided on the surface of the P2 layer. In addition, from the viewpoint of suppressing the light scattering of the resist light, it is also preferred not to contain particles with an average primary particle size of 200 nm or more. As the particles contained in the above-mentioned P2 layer, it is more preferred not to contain particles with an average primary particle size of 150 nm or more, further preferably not to contain particles with an average primary particle size of 100 nm or more, and most preferably not to contain particles with an average primary particle size of 70 nm or more.
[0085] The surface of the P2 layer of the present invention has protrusions, and the number of protrusions having a height of 10 nm or more measured by a scanning white interference microscope according to the method described later is set as N. 10nm (pcs / mm 2 ) 10nm When the biaxially oriented polyester film of the present invention is used as a film for a dry film resist support, N 10nm The number of fine protrusions N formed on the surface of the P2 layer is a value that affects the mobility of the P2 layer. 10nm (pcs / mm 2 ) is 600 or more, so that even if particles with an average primary particle size of 200 nm or more are not used in the P2 layer, mobility with the conveying roller can be ensured in the manufacturing process of the biaxially oriented polyester film, and the generation of surface scratches can be suppressed. In addition, the number N of protrusions with a height of 10 nm or more is 10nm (pcs / mm 2 ) is less than 12000, so that the interface roughness between the P2 layer surface and the resist layer can be suppressed, and the resist light is scattered at the above interface. As the number N of protrusions with a height of more than 10 nm 10nm (pcs / mm 2 ), and more preferably 1000 or more, as the number N of protrusions with a height of 10 nm or more 10nm (pcs / mm 2 ), and more preferably, it is 10,000 or less.
[0086] As the number N of protrusions with a height of 10 nm or more measured by a scanning white interference microscope on the surface of the P2 layer of the present invention, 10nmThe method for the above range includes a method of adding particles having a specific particle size described later, a method of transferring a shape on a surface using a mold such as nanoimprinting, and a method of biaxially stretching an unstretched sheet after surface treatment with plasma using atmospheric pressure glow discharge. Among them, from the viewpoint of improving the mobility of the biaxially oriented polyester film of the present invention, it is preferred to use any one of a method of biaxially stretching by plasma treatment using atmospheric pressure glow discharge and a method of containing minute particles described later. From the viewpoint of not reducing the optical properties facing the fine resist wiring and suppressing the deposition of degraded products such as oligomers generated by high-temperature heat treatment in the above-mentioned biaxially oriented polyester film manufacturing process on the surface and floating (lamination voids) during lamination, it is preferred to use a method of biaxially stretching by plasma treatment using atmospheric pressure glow discharge, or a method of biaxially stretching by plasma treatment using atmospheric pressure glow discharge and a method of containing minute particles described later.
[0087] Plasma surface treatment using atmospheric pressure glow discharge (hereinafter sometimes referred to as atmospheric pressure plasma treatment) can be applied to the polyester film manufacturing process in the state of the unstretched film after extrusion, or it can be applied to the film after stretching. However, from the viewpoint of imparting smoothness to the surface of the P2 layer and also imparting lubricity, it is most preferred to apply plasma surface treatment using atmospheric pressure glow discharge in the state of the unstretched film. This is because the amorphous polyester part is shaved off by the plasma surface treatment using atmospheric pressure glow discharge, and the crystalline polyester part remaining on the surface grows as a convex part in the subsequent stretching film-making process to form fine protrusions on the surface. In addition, the crystal growth of the polyester film accompanied by the plasma surface treatment using atmospheric pressure glow discharge is carried out, so that the existence ratio of the crystallized domains densely filled with molecular chains on the film surface increases, thereby showing an effect of preventing oligomers generated by heat treatment, etc. from precipitating from the inside of the film to the surface.
[0088] The atmospheric pressure here is in the range of 700 torr to 780 torr. Atmospheric pressure glow discharge treatment is a process in which a film to be treated is introduced between an opposing electrode and a grounded roller, a plasma excitation gas is introduced into the device, and a high-frequency voltage is applied between the electrodes to excite the gas to plasma and perform glow discharge between the electrodes. As a result, the film surface is finely processed (polished) to form protrusions.
[0089] The so-called plasma excitation gas refers to a gas that can be excited by plasma under the above-mentioned conditions. Examples of the plasma excitation gas include rare gases such as argon, helium, neon, krypton, and xenon, nitrogen, carbon dioxide, oxygen, or chlorofluorocarbons such as tetrafluoromethane, and mixtures thereof. In addition, the plasma excitation gas may be used alone or in combination of two or more in any mixing ratio.
[0090] The frequency of the high frequency voltage in the plasma treatment is preferably in the range of 1 kHz to 100 kHz. In addition, the discharge treatment intensity (E value) obtained by the following method is in the range of 50 to 1000 W·min / m 2 It is preferred to treat in the range of 150 to 800 W·min / m from the viewpoint of protrusion formation, and more preferably 150 to 800 W·min / m 2 . The discharge treatment intensity (E value) is 50W·min / m 2 The above can fully form the protrusions, and the discharge treatment intensity (E value) is 1000W·min / m 2 As a result, excessive damage to the polyester film can be suppressed and the generation of foreign matter on the surface can be reduced.
[0091] <How to calculate the discharge treatment intensity (E value)>
[0092] E=Vp×Ip / (S×Wt)
[0093] E: E value (W·min / m 2 )
[0094] Vp: Applied voltage (V)
[0095] Ip: Applied current (A)
[0096] S: Processing speed (m / min)
[0097] Wt: processing width (m).
[0098] Generally, when polishing the surface of a polyester film, especially a film having an amorphous part and a crystalline part such as PET or PEN, by atmospheric pressure glow discharge treatment, polishing is performed from the soft amorphous part. By subdividing the crystalline part and the amorphous part, finer protrusions can be formed by atmospheric pressure glow discharge treatment, and the above-mentioned N 10nm Increase.
[0099] Regarding the particles contained in the above-mentioned P2 layer, either inorganic particles or organic particles can be used, or more than two kinds of particles can be used in combination. However, as mentioned above, regarding the particles contained in the P2 layer, it is preferred to use particles with an average primary diameter of less than 200nm, more preferably particles with an average primary diameter of less than 150nm, further preferably particles with an average primary diameter of less than 100nm, and most preferably particles with an average primary diameter of less than 70nm.
[0100] As inorganic particles that can be used, for example, calcium carbonate, magnesium carbonate, zinc carbonate, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, zinc sulfide, calcium phosphate, aluminum oxide (α aluminum oxide, β aluminum oxide, γ aluminum oxide, δ aluminum oxide), mica, mica, titanium mica, zeolite, talc, clay, kaolin, lithium fluoride, calcium fluoride, montmorillonite, zirconium oxide, silicon dioxide (wet silicon dioxide, dry silicon dioxide, colloidal silicon dioxide) etc. can be cited. As organic particles, examples can be given such as organic particles, core-shell organic particles etc. with acrylic resin, styrene resin, silicone resin, polyimide resin etc. as constituent components. Wherein for inorganic particles, aluminum oxide is preferred because it has a high Mohs hardness and suppresses the effect of film surface damage, and in addition for organic particles, it is preferred because styrene resin is close to the refractive index of biaxially oriented polyester film.
[0101] In the biaxially oriented polyester film of the present invention, when the intrinsic viscosity (IV) of the entire P2 layer is IV P2 (dl / g), IV P2 (dl / g) is preferably 0.50 or more and 0.63 or less. IV is a number reflecting the length of the molecular chain. When the molecular chain is short, the polyester molecules are easily oriented / crystallized during stretching / heat treatment. P2 When (dl / g) is 0.63 or less, when the atmospheric pressure plasma treatment is used, the formation of protrusions in the biaxial stretching film-forming step can be promoted, thereby improving the mobility.
[0102] In addition, by making IV P2 When the molecular weight is 0.50 dl / g or more, oligomers generated by heat treatment can be minimized while applying no pressure when the polyester resin is melt-extruded, thereby preventing film breakage due to the generation of bubbles and preventing biaxial stretching from becoming difficult.
[0103] In the biaxially oriented polyester film of the present invention, the thickness of the P2 layer is defined as T P2 (μm), T P2 It is preferably 0.2 or more and 2.0 or less. P2(μm) is 0.2 or more, so that the effect of protrusion formation brought about by the plasma treatment using atmospheric pressure glow discharge can be efficiently obtained when the P2 layer contains particles or the intrinsic viscosity is controlled. P2 (μm) is 2.0 or less, which is more preferable from the viewpoint of suppressing the decrease in the optical characteristics of the entire film. P2 The upper limit of (μm) is more preferably 1.5 or less.
[0104] (Middle layer: P3 layer)
[0105] The biaxially oriented polyester film for a dry film resist support of the present invention may include a P3 layer containing particles at a lower concentration than the P1 layer or containing no particles, between the moving surface layer (P1 layer) containing the above particles and the (P2 layer) having protrusions.
[0106] From the viewpoint of improving the optical properties of the biaxially oriented polyester film, the above-mentioned P3 layer preferably has a lower particle concentration than the P1 layer, or does not contain particles. In addition, by making the amount of particles contained in the P3 layer as described above, the addition of raw materials in a state of thermal degradation such as master batches containing particles and recycled raw materials of film containing particles once melt-extruded can be suppressed to a minimum, and the generation of degraded products such as oligomers during high-temperature heat treatment can be suppressed, which is preferred from this viewpoint. The so-called recycled raw materials here refer to raw materials in a granular state after the polyester film that has been film-formed once is crushed. Since the recycled raw materials can reuse the film discharged as scraps during film-forming, they can be used to reduce the cost of the product, but on the other hand, compared with the new polyester resin flakes, they are subjected to thermal damage during film-forming and re-granulation, and the generation of degraded products is worsened when the P3 layer is added.
[0107] The P3 layer in the biaxially oriented polyester film preferably has a lower particle concentration than the P1 layer, a lower content concentration of particles having an average primary particle size of 70 nm to 200 nm than the P1 layer, or contains no particles.
[0108] Furthermore, when the intrinsic viscosity of the polyester resin constituting the P2 layer is controlled within the above-mentioned preferred range, from the viewpoint of improving the overall mechanical properties of the polyester film, the above-mentioned P3 layer is preferably composed of three layers of P1 layer / P3 layer / P2 layer composed of a polyester resin having an intrinsic viscosity (IV) of not less than 0.55.
[0109] In the biaxially oriented polyester film of the present invention, the number of coarse particles having a major diameter of 2.0 μm or more existing in a region 3 μm away from the P1 layer in the film thickness direction observed by an optical microscope is defined as N. P1 (pcs / 8.25mm 2) is preferably N P1 The number N of coarse particles with a major diameter of 2.0 μm or more existing in a region of 3 μm in the film thickness direction is 20 or less. P1 (pcs / 8.25mm 2 ) is a value reflecting the number of aggregated particles contained in the P1 layer and even in the P3 layer as an intermediate layer when the thickness of the P1 layer is less than 3 μm. P1 10 pieces / 8.25mm 2 As a result, the generation of pinhole defects can be suppressed even in the next generation of fine resist wiring (L / S 5 / 5 μm). P1 (pcs / 8.25mm 2 ) is preferably in the range of 10 or less, and more preferably in the range of 8 or less.
[0110] As the number N of coarse particles with a major diameter of 2.0 μm or more existing in the region 3 μm away from the P1 layer in the film thickness direction, P1 (pcs / 8.25mm 2 ) is a preferred range, which is a method of filtering the polymer melted and extruded by an extruder through a filter. If particles contained in the biaxially oriented polyester film, catalyst residues when the polyester resin is polymerized, and extremely small foreign matter mixed from the outside of the film-making process also enter the film, they will become coarse protrusion defects, so it is effective to use a high-precision filter that can capture foreign matter of 2μm or more or 5μm or more by 95% or more. In addition, when a particle masterbatch is used when the biaxially oriented polyester film of the present invention contains particles, it is a more preferred mode to use the same filter when preparing the particle masterbatch.
[0111] (Method for producing biaxially oriented polyester film)
[0112] Next, the method for producing the biaxially oriented polyester film of the present invention will be described with reference to examples, but the present invention is not limited to those obtained by these examples.
[0113] As a method for obtaining the polyester film used in the present invention, a polymerization method based on a conventional method can be adopted. For example, it can be obtained by subjecting a dicarboxylic acid component such as terephthalic acid or its ester-forming derivatives to an ester exchange reaction or esterification reaction with a diol component such as ethylene glycol or its ester-forming derivatives by a known method, followed by melt polymerization. In addition, as required, the polyester obtained by the melt polymerization reaction can be subjected to a solid phase polymerization reaction at a temperature below the melting point of the polyester.
[0114] The polyester film of the present invention can be obtained by a conventionally known manufacturing method. Specifically, the polyester film of the present invention can be obtained by heating and melting the raw material dried as required in an extruder, extruding it from a die onto a cooled casting drum to form a sheet (melt casting method). As another method, a method in which the raw material is dissolved in a solvent, the solution is extruded from a die onto a support such as a casting drum or an endless belt to form a film, and then the solvent is dried and removed from such a film layer to form a sheet (solution casting method) can be used.
[0115] In the case of manufacturing a biaxially oriented polyester film of two or more layers by melt casting, the following method is suitable: each layer constituting the biaxially oriented polyester film uses an extruder, melts the raw materials of each layer, and laminates them in a molten state by a confluence device provided between the extruder and the die, and then guides them to the die, and extrudes them from the die onto the casting drum to form a sheet (coextrusion method). The laminated sheet is closely attached to the casting drum cooled to a surface temperature of 20°C or more and 60°C or less by static electricity, and then cooled and solidified to produce an unstretched film. By making the surface temperature of the casting drum above 20°C, the crystalline polyester part of the surface of the unstretched film can be further increased, and the effect of forming fine protrusions after stretching brought about by the plasma surface treatment using atmospheric pressure glow discharge can be obtained. In addition, by making the surface temperature of the casting drum below 60°C, the adhesion of the unstretched film to the casting drum can be suppressed, and an unstretched film with less uneven thickness along the film moving direction can be obtained. The more preferred range of the surface temperature of the casting drum is 25°C or more and 55°C or less.
[0116] Next, the unstretched film obtained here is subjected to surface treatment such as plasma surface treatment using atmospheric pressure glow discharge. These surface treatments may be after the unstretched film is just obtained, or after it is stretched along the moving direction of the film (hereinafter, sometimes referred to as the longitudinal direction), but in the present invention, it is preferred to perform surface treatment on the unstretched film from the viewpoint of further promoting the formation of the above-mentioned protrusions. In addition, the surface subjected to surface treatment may be any one of the surface (drum surface) in contact with the casting drum and the surface (non-drum surface) not in contact with the casting drum.
[0117] (Sequential biaxial stretching)
[0118] Regarding the stretching conditions when the unstretched film is biaxially stretched, in the case where the polyester film of the present invention has polyester as the main component, as the stretching in the longitudinal direction, it is preferred that the unstretched film is guided to a roller group heated to 70°C or more, stretched in the longitudinal direction (longitudinal direction, i.e., the traveling direction of the film), and cooled with a roller group set to a temperature of 20°C or more and 50°C or less. There is no particular restriction on the lower limit of the temperature of the heating roller in the stretching in the longitudinal direction as long as the stretchability of the sheet is not impaired, but it is preferably higher than the glass transition temperature of the polyester resin used. In addition, the preferred range of the stretching ratio in the longitudinal direction is 3.0 times or more and 4.8 times or less. As a more preferred range, it is 3.5 times or more and 4.8 times or less. If the stretching ratio in the longitudinal direction is 3.0 times or more, orientation crystallization proceeds and the film strength can be improved. On the other hand, by setting the stretching ratio to 4.8 times or less, the dimensional change rate ΔL when the temperature is increased from 90°C to 130°C in the direction perpendicular to the longitudinal direction (width direction) can be reduced. 90-130℃ (ppm / °C) is controlled within a preferred range, and it is possible to suppress the frequent occurrence of film breakage during production due to excessive orientation, thereby suppressing a decrease in productivity.
[0119] It is preferred that the obtained uniaxially stretched film stretched in the longitudinal direction is guided to a tenter while being held at both ends by clamps, and stretched by 3 times or more and 5 times or less in a direction (width direction) perpendicular to the longitudinal direction in an atmosphere heated to a temperature of 70°C to 160°C.
[0120] Then, the stretched film is preferably subjected to a heat treatment to stabilize the internal orientation structure. The thermal history temperature to which the film is subjected during the heat treatment can be confirmed by the temperature of a small endothermic peak (sometimes referred to as Tmeta) that appears just below the melting point temperature measured by a differential scanning calorimeter (DSC) described later. In general, since Tmeta represents a value of about -5°C of the heat treatment temperature, the thermal history applied to the film can be inferred from this value. Furthermore, for the purpose of imparting dimensional stability, a relaxation treatment is preferably performed after the heat treatment. Regarding the conditions for the heat treatment and the relaxation treatment, the dimensional change rate ΔL when the temperature is raised from 90°C to 130°C in the above-mentioned direction is as follows. 90-130℃ (ppm / °C) is controlled within the preferred range.
[0121] The stretching ratio is 3 times or more and 4.8 times or less in the length direction and the width direction, respectively, and the area ratio (stretching ratio in the length direction×stretching ratio in the width direction) is preferably 9 times or more and 22 times or less, and more preferably 9 times or more and 20 times or less. By setting the area ratio to 9 times or more, the molecular orientation of the obtained biaxially oriented polyester film can be promoted to improve the durability, and by setting the area ratio to 22 times or less, the occurrence of rupture during stretching can be suppressed.
[0122] [Evaluation method of characteristics]
[0123] A. Evaluation using a scanning white interference microscope (VertScan)
[0124] A 6 cm × 6 cm sample was taken from the biaxially oriented polyester film. For each sample, a scanning white interference microscope (device: "VertScan" (registered trademark) VS1540 manufactured by Hitachi High Tech Science Co., Ltd.) was used. For the surface of the biaxially oriented polyester film, a 50x objective lens was used, and the measurement mode was set to WAVE mode. 90 fields of view were measured with a measurement area of 113 μm × 113 μm. The sample was placed on the stage for measurement in such a way that the Y axis became the length direction of the sample film (the direction in which the film was wound). It should be noted that in the case of a sample whose length direction is unknown, the Y axis was measured in any one direction of the sample film, and then it was measured in a direction rotated 120 degrees, and then it was measured in a direction rotated 120 degrees, and the average of the respective measurement results was set as the number of protrusions possessed by the sample. The sample film to be measured was sandwiched between two metal frames with rubber gaskets, so that the film in the frames was in a tense state (a state where slack and curl of the sample were eliminated) and the sample surface was measured.
[0125] The obtained microscope image was subjected to image processing under the following conditions using surface analysis software VS-Viewer Version 10.0.3.0 built into the microscope to determine the root mean square roughness and the number of protrusions of each height.
[0126] (Image processing conditions)
[0127] Image processing is performed in the following order.
[0128] Interpolation processing: Full interpolation
[0129] Filter processing: median (3×3 pixels)
[0130] ·Surface correction: 4 times.
[0131] (i) Root mean square roughness (Sq)
[0132] The surface of the biaxially oriented polyester was measured by scanning white interference microscopy in 90 viewing fields, and the root mean square roughness Sq (nm) was obtained by outputting the numerical value group obtained by selecting "Height Parameters" in the "ISO parameter" analysis in the surface analysis software together with the following analysis conditions to the parameter table column for each measurement image subjected to the above image processing, and the average value of the 90 viewing fields was set as the root mean square roughness Sq (nm) of the measurement surface. The root mean square roughness of the surface of the P1 layer obtained by the above method was set as Sq P1 (nm), and the root mean square roughness of the surface of the above-mentioned P2 layer is set to SqP2 (nm).
[0133] (ISO parameter analysis conditions)
[0134] The ISO parameter analysis process was performed under the following conditions.
[0135] S-Filter: Automatic
[0136] Normal probability paper
[0137] Number of divisions: 300
[0138] Upper limit of calculation range: 3.000
[0139] Lower limit of calculation range: -3.000
[0140] Parameters: Select "Height Parameters"
[0141] Output: Select "Parameter List"
[0142] (Parameter table output)
[0143] By selecting "Height Parameters" in the "ISO Parameters" window displayed by the above-mentioned ISO parameter analysis and "Add to Parameter Table", "Sq [μm]" displayed in the "ISO Parameters" tab of the "Parameter Table" window is converted into nm units for use.
[0144] (ii) Number of protrusions with a height of 10 nm or more (N 10nm )
[0145] After the surface (A surface) was observed and processed under the microscope as described above, particle analysis was performed under the following conditions using the surface analysis software VS-Viewer Version 10.0.3.0 built into the microscope. 50nmThe number of protrusions with a height of 10 nm or more was calculated by dividing the number of particles detected and displayed on the "Particle Analysis" screen by the measurement area (113 μm × 113 μm) (height threshold setting value: 0.01 μm) (particles / mm 2 ).
[0146] The same operation is performed for all 90 measured fields of view, and the average value thereof is set as the number N of protrusions with a height of 10 nm or more on the A surface of the sample. 10nm (pcs / mm 2 ).
[0147] (Particle analysis conditions)
[0148] The protrusion analysis process was performed under the following conditions.
[0149] Analysis type: sudden analysis
[0150] Image correction: No
[0151] ·deal with
[0152] Height threshold: 0.01μm
[0153] Particle shaping: No
[0154] Reference height: zero plane (average plane)
[0155] ·Judgment object
[0156] Height / depth: -10000μm≤h≤10000μm
[0157] The longest diameter: -10000μm≤d≤10000μm
[0158] Volume: V ≥ 0.0000 μm 3
[0159] Aspect ratio: r ≥ 0.0000
[0160] Histogram: Number of divisions 50
[0161] (Reference height: zero plane (average plane))
[0162] As the "zero plane (average plane)" in the above-mentioned reference height (height 0 nm) setting, the plane of the "average height (Ave)" automatically calculated by the following formula in the measurement image (113 μm×113 μm) obtained by microscope image observation and image processing according to the above-mentioned method is used.
[0163]
[0164] lx: The range length in the X direction of each measurement image subjected to the above image processing
[0165] ly: The range length in the Y direction of each measurement image subjected to the above image processing
[0166] h(x, y): The height of each image point (x, y) in the measured image after the above image processing.
[0167] B. Thermal dimensional change rate ΔL (ppm / ℃)
[0168] (i) Thermomechanical analysis (TMA)
[0169] The measurement was performed in the following manner using a thermomechanical measuring apparatus TMA / SS6000 (manufactured by Seiko Instruments) and attached analysis software TMA / SS6100 (manufactured by Seiko Instruments).
[0170] The biaxially oriented polyester film was cut into a strip having a length of 30 mm in the measuring direction and 4 mm in the direction perpendicular to the measuring direction, and was attached to the device with a distance between chucks of 20 mm in the measuring direction.
[0171] Then, in a temperature-controlled furnace (tank), with a tension of 29.4 mN applied along the measuring direction of the sample, the temperature in the furnace was increased from 25°C to 180°C at a heating rate of 10°C / min and then maintained for 10 minutes. The thermal dimensional change rate ΔL (ppm / °C) of the biaxially oriented polyester film was calculated from the dimensions at each film temperature, i.e., the distance between the chucks.
[0172] The film temperature here refers to the tank temperature (Temp Cel) recorded every 20 seconds when measuring using the attached analysis software TMA / SS6100 (manufactured by Seiko Instruments Co., Ltd.). In addition, the distance between chucks refers to the TMA length (TMA μm) recorded when measuring using the attached analysis software TMA / SS6100 (manufactured by Seiko Instruments Co., Ltd.).
[0173] (ii) Thermal dimensional change rate ΔL during the process of heating from 90°C to 130°C 90-130℃
[0174] According to the above item (i), the thermal dimensional change rate ΔL in the process of heating from 90°C to 130°C was calculated from the film dimensions at film temperatures of 90°C and 130°C using the following formula (1): 90-130℃ The measurement was performed twice and the average value thereof was defined as the thermal dimensional change rate ΔL of the biaxially oriented polyester film in the step of heating from 90° C. to 130° C. 90-130℃ (ppm / ℃).
[0175] ΔL 90-130℃ (ppm / °C) = [(film size at 130°C (μm)) - (film size at 90°C (μm))] / [130°C - 90°C] × 10000 (1)
[0176] The ΔL in the width direction and the length direction of the biaxially oriented polyester film was measured to obtain the ΔL in the width direction and the length direction. 90-130℃ (ppm / ℃).
[0177] When the direction of the polyester film is unclear, after measuring in any direction, measure in every 45 degrees shifted direction to confirm whether there is a direction satisfying the structure of the present application, and set ΔL 90-130℃ The direction in which (ppm / °C) satisfies -50 or more and 150 or less is defined as the width direction.
[0178] (iii) Thermal dimensional change rate ΔL in the process of heating from 90°C to 110°C 90-110℃
[0179] According to the above item (i), the thermal dimensional change rate ΔL in the process of heating from 90°C to 110°C was calculated from the film dimensions at film temperatures of 90°C and 110°C using the following formula (2): 90-110℃ The measurement was performed twice and the average value thereof was defined as the thermal dimensional change rate ΔL of the biaxially oriented polyester film in the step of heating from 90° C. to 110° C. 90-110℃ (ppm / ℃).
[0180] ΔL 90-130℃ (ppm / °C) = [(film size at 110°C (μm)) - (film size at 90°C (μm))] / [110°C - 90°C] × 10000 (2)
[0181] The ΔL in the width direction of the biaxially oriented polyester film was measured to determine the ΔL in the width direction. 90-130℃ (ppm / ℃).
[0182] (iv) Thermal dimensional change rate ΔL in the process of heating from 110°C to 130°C 110-130℃
[0183] According to the above item (i), the thermal dimensional change rate ΔL in the process of increasing the temperature from 110°C to 130°C was calculated using the following formula (2) from the film dimensions at film temperatures of 90°C and 110°C: 110-130℃ The measurement was performed twice and the average value thereof was defined as the thermal dimensional change rate ΔL of the biaxially oriented polyester film in the step of heating from 110° C. to 130° C. 110-130℃ (ppm / ℃).
[0184] ΔL 110-130℃ (ppm / °C)=[(film size at 130°C (μm))-(film size at 110°C (μm))] / [130°C-110°C]×10000···(2)
[0185] The ΔL in the width direction of the biaxially oriented polyester film was measured to determine the ΔL in the width direction. 90-130℃ (ppm / ℃).
[0186] C. Film thickness
[0187] (i) Total film thickness T
[0188] The total thickness of the biaxially oriented polyester film was measured at five random locations using a direct-reading thickness meter in accordance with JIS K7130 (1992) A-2 method with 10 films stacked together. The average value was divided by 10 to give the total film thickness T (μm).
[0189] (ii) Layer thickness (T P1 、T P2 、T P3 )
[0190] The cross section of the biaxially oriented polyester film is cut out in a direction parallel to the film width direction using a microtome. The cross section is observed with a scanning electron microscope at a magnification of 5000 to 20000 times to determine the thickness ratio of each laminated layer. The thickness of each layer is calculated from the obtained laminate ratio and the total film thickness obtained in the above item (i).
[0191] D. Polymer properties
[0192] (i) Intrinsic viscosity (IV)
[0193] The sample to be measured (polyester resin (raw material) or the polyester film of the present invention) was dissolved in 100 ml of o-chlorophenol (solution concentration C (sample weight / solution volume) = 1.2 g / 100 ml), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. In addition, the viscosity of the solvent was measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated by the following formula (1), and the obtained value was set as the intrinsic viscosity (IV) of the entire polyester film.
[0194] ηsp / C=[η]+K[η] 2 ·C···(1)
[0195] (Here, ηsp = (solution viscosity / solvent viscosity) - 1, and K is the Huggins constant (set to 0.343).)
[0196] In addition, when the solution in which the measurement sample was dissolved contained insoluble matter such as inorganic particles, the measurement was performed using the following method.
[0197] (1-1) A measurement sample is dissolved in 100 mL of o-chlorophenol to prepare a solution having a concentration higher than 1.2 g / 100 mL. Here, the weight of the measurement sample provided to o-chlorophenol is referred to as the measurement sample weight.
[0198] (1-2) Next, the solution containing the insoluble matter is filtered, and the weight of the insoluble matter and the volume of the filtrate after filtration are measured.
[0199] (1-3) Add o-chlorophenol to the filtrate after filtration and adjust the ratio of (measured sample weight (g) - weight of insoluble matter (g)) / (volume of filtrate after filtration (mL) + volume of o-chlorophenol added (mL)) to 1.2 g / 100 mL.
[0200] (For example, when a concentrated solution with a sample weight of 2.0 g / solution volume of 100 mL is prepared, when the weight of the insoluble matter when the solution is filtered is 0.2 g and the volume of the filtrate after filtration is 99 mL, an adjustment is performed by adding 51 mL of o-chlorophenol. ((2.0 g - 0.2 g) / (99 mL + 51 mL) = 1.2 g / 100 mL)
[0201] (1-4) The solution obtained in (1-3) is used to measure the viscosity at 25° C. using an Ostwald viscometer. The obtained solution viscosity and solvent viscosity are used to calculate [η] using the above formula (5), and the obtained value is defined as the intrinsic viscosity (IV).
[0202] (ii) Intrinsic viscosity of the masterbatch (IV MP )
[0203] The intrinsic viscosity (IV) of the master batch used as a raw material of the biaxially oriented polyester film of the present invention was obtained in the same manner as in the above item (i). MP ).
[0204] (iii) Intrinsic viscosity of polyester resin (IV PET )
[0205] The polyester resin used as a raw material of the biaxially oriented polyester film of the present invention was subjected to the same operation as in the above item (i) to obtain the intrinsic viscosity (IV) of the polyester resin. PET ).
[0206] (iv) Intrinsic viscosity of biaxially oriented polyester film (IV)
[0207] The biaxially oriented polyester film of the present invention was measured in the same manner as in the above item (i) to obtain the intrinsic viscosity (IV) of the biaxially oriented polyester film.
[0208] E. Evaluation of particles contained
[0209] (i) Particle Observation
[0210] Regarding the biaxially oriented polyester film of the present invention, a small piece cut in a direction perpendicular to the surface is prepared using a microtome, and its cross section is observed using the following TEM (transmission electron microscope: H7100FA manufactured by Hitachi, Ltd.) at 10,000 to 100,000 times to obtain a cross-sectional photograph containing particles.
[0211] Measurement device: Transmission electron microscope (TEM) Hitachi H-7100FA
[0212] Measurement conditions: Acceleration voltage 100 kV
[0213] Measurement magnification: 200,000 times to 800,000 times
[0214] Sample conditioning: ultra-thin film sectioning method (RuO4 staining).
[0215] (ii) Average primary particle size (peak diameter D1 (nm))
[0216] The particle size distribution of particles present in the P1 layer, P2 layer or P3 layer was obtained by using the image analysis software Image-ProPlus (Japan Ropa (Strain)) from the cross-sectional photograph obtained by the method described in (i) above. The cross-sectional image was selected from different arbitrary measurement fields, and the equivalent circular diameter of each particle was measured for more than 400 particles present in the cross-sectional image. Regarding the equivalent circular diameter of the obtained particles, a number-based particle size distribution measurement was performed with the horizontal axis set to the particle size (equivalent circular diameter) and the vertical axis set to the existence ratio of the particles, and the particle size (equivalent circular diameter) showing the maximum peak top was set to the average primary particle peak diameter D1 (nm). At this time, in the case of confirming that agglomerated particles are connected in a plurality of particles, the equivalent circular diameter of each particle constituting the agglomerated particles (the smallest particle that cannot be divided into particles) is obtained, and the number-based particle size distribution measurement is performed using this value.
[0217] When the biaxially oriented polyester film contains two or more particles having different particle sizes, the number-based particle size distribution has two or more peaks. In this case, each peak value is defined as the average primary particle size (peak diameter D1) of each particle.
[0218] (iii) Particle concentration
[0219] 1 g of a sample from which only the P1 layer, P2 layer, and P3 layer of the biaxially oriented polyester film of the present invention were cut off was put into 200 ml of 1N-KOH methanol solution and heated under reflux to dissolve the polymer. 200 ml of water was added to the solution after dissolution, and the liquid was then supplied to a centrifuge to settle the particles and remove the supernatant. Water was further added to the particles and washing and centrifugation were repeated twice. The particles obtained by the above operation were dried, and their mass (g) was measured to calculate the concentration (mass %) of the particles contained in each layer of the biaxially oriented polyester film.
[0220] In the case where the particles contain organic particles, a solvent in which the polymer is dissolved but the organic particles are not dissolved is selected, the polymer is dissolved without heating and refluxing, and the particles are centrifuged to calculate the particle content (mass %) of each layer. Whether the contained particles are organic particles or inorganic particles can be confirmed by whether inorganic matter is detected when the particles are observed by generally known methods such as SEM-EDX.
[0221] F. Film haze evaluation
[0222] (i) Initial haze (H0)
[0223] The biaxially oriented polyester film was sampled into 5 cm squares and the haze (%) in the thickness direction was measured using a fully automatic direct-reading haze computer HGM-2DP (manufactured by Suga Testing Instruments Co., Ltd.). The average of the measured values in three tests was calculated as the initial haze (H0) of the biaxially oriented polyester film.
[0224] (ii) Haze after heat treatment (H1)
[0225] The 5 cm square sample used in the previous item (i) was placed in an oven maintained at 150°C, and an accelerated test of heat treatment was performed for 1 hour. Then, after being taken out of the oven and cooled to room temperature, the haze of the film after heat treatment was measured in the same manner as in the previous item (i). The average of the measured values in the three tests was defined as the haze (H1) of the biaxially oriented polyester film after heat treatment.
[0226] The haze increase (ΔH) before and after the heat treatment at 150° C. for 1 hour was determined using the following formula (2).
[0227] ΔH=H1-H0···(2)
[0228] G. Evaluation of the number of coarse particles in the P1 layer
[0229] The biaxially oriented polyester film of the present invention is cut into pieces of 11 mm×0.75 mm (8.25 mm 2), using an optical microscope (ECLIPSE LV100 manufactured by Nikon), after focusing on the film surface, the focus was shifted to the inner side of the film in the film thickness direction, and the area from the film surface to 3 μm in the film thickness direction was observed, and the number of coarse particles with a long diameter of 2.0 μm or more existing in the area 3 μm away from the film surface in the film thickness direction was measured. The number of measurements was set to n=3, and the average value of them was set to the number of coarse particles N in the sample. P1 (pcs / 8.25mm 2 ).
[0230] [Evaluation method of application characteristics]
[0231] A. Membrane productivity
[0232] (i) Evaluation of corrugation and wrinkles
[0233] The biaxially oriented polyester film of the present invention was wound 10 times at a speed of 100 m / min or more into a biaxially stretched film roll having a width of 2000 mm or more and a winding length of 4000 m or more. The number of wavy wrinkles (wavy wrinkles) having a height of 5 mm or more in the width direction over a length of 10 m or more in the 10 film slit rolls obtained was evaluated as follows.
[0234] A: Among 10 rolls, one or less rolls had corrugated wrinkles.
[0235] B: Among 10 rolls, 2 or more and 3 or less rolls have corrugated wrinkles.
[0236] C: Among 10 rolls, 4 or more and 6 or less rolls have corrugated wrinkles.
[0237] D: Among 10 rolls, 7 or more rolls have corrugated wrinkles.
[0238] As for the evaluation of corrugation wrinkles, A to C were good, and A was the most excellent.
[0239] (ii) Evaluation of winding wrinkles
[0240] The 10 rolls obtained in the above item (i) without corrugation wrinkles were slit at a speed of 130 m / min or more to a width of 1000 mm, and 10 continuous slit rolls of 4000 m were taken and wound up. Based on the winding appearance of the 10 film slit rolls obtained, the occurrence of roll wrinkles was evaluated as follows.
[0241] A: Among 10 rolls, one or less rolls had winding wrinkles.
[0242] B: Among 10 rolls, the number of rolls having winding wrinkles is 2 or more and 3 or less.
[0243] C: Among 10 rolls, 4 or more and 6 or less rolls have winding wrinkles.
[0244] D: Among 10 rolls, 7 or more rolls have winding wrinkles.
[0245] As for the evaluation of winding wrinkles, A to C were good, and A was the most excellent.
[0246] (iii) Surface damage assessment
[0247] 10 m of the surface layer of each of the 10 slit rolls obtained in the above (ii) was unwound, and a film sample with a width of 1000 mm and a length of 1 m (a position 10 m to 11 m unwound from the surface layer) was taken. The surface of the obtained 10 roll film samples was observed, and surface scratches were confirmed by visual inspection. The surface scratches of each roll were evaluated as follows.
[0248] A: Among 10 rolls, less than 1 roll had surface scratches.
[0249] B: Among 10 rolls, 2 or more and 3 or less rolls had surface scratches.
[0250] C: Among 10 rolls, 4 or more and 6 or less rolls had surface scratches.
[0251] D: Among 10 rolls, 7 or more rolls have surface scratches.
[0252] As for the surface scratch evaluation, A to C were good, and A was the most excellent.
[0253] B. Evaluation of high temperature lamination processing adaptability
[0254] (i) Resist layer coating and lamination processing
[0255] A resist layer was provided on the biaxially oriented polyester film by the following methods ab, and a lamination process was performed.
[0256] a. Regarding the sample of the biaxially oriented polyester film of the present invention with a width of 200 mm and a length of 1 m or more, a photosensitive resin layer was coated on the surface of the P2 layer in a dark room by a gravure coating method in such a way that the coating thickness became 15 μm. As the photosensitive resin layer, a mixture consisting of a copolymer formed of methacrylic acid, methyl methacrylate, ethyl acrylate, and butyl methacrylate as a thermoplastic resin, trimethylolpropane triacrylate and polyethylene glycol (number average molecular weight 600) dimethacrylate as a photosensitive material, benzophenone and dimethylaminobenzophenone as a photopolymerization initiator, hydroquinone as a stabilizer, and methyl violet as a colorant was used.
[0257] b. The anti-etching layer surface of the obtained biaxially oriented polyester film sample provided with an anti-etching layer was overlapped in a manner in which it was in contact with a metal substrate (copper foil substrate) bonded with a 3 μm thick copper foil cut into A4 size, and then laminated under the following conditions using a laminator equipped with a temperature-controllable rubber pressure roller.
[0258] (Lamination Processing Conditions)
[0259] Lamination conveying speed: 2m / min
[0260] Lamination roller temperature: 100℃, and 120℃
[0261] Lamination pressure: 0.5MPa
[0262] The lamination process adaptability at 100°C was evaluated by visually confirming the A4-sized laminated sample of the copper foil substrate and the biaxially oriented polyester sample when the lamination roll temperature was set to 100°C, and the lamination process adaptability at 120°C was evaluated by visually confirming the laminated sample of the copper foil substrate and the biaxially oriented polyester sample when the lamination roll temperature was set to 120°C.
[0263] (ii) 100°C Lamination Void Evaluation
[0264] For 10 A4-sized laminated samples of copper foil substrates and biaxially oriented polyester samples laminated at a lamination roll temperature of 100°C obtained in the previous items (i) a. to b., the presence or absence of lamination voids (floating of the lamination layer) was visually confirmed, and the number of samples with the major diameter of the voids exceeding 1 mm was evaluated as follows.
[0265] A: Lamination voids occurred in less than 1 sheet among 10 sheets of laminated samples.
[0266] B: Among the 10 laminated samples, lamination voids occurred in 2 or more and 3 or less sheets.
[0267] C: Among the 10 laminated samples, lamination voids occurred in 4 or more and 6 or less sheets.
[0268] D: Lamination voids occurred in 7 or more sheets among 10 sheets of laminated samples.
[0269] As for the lamination void evaluation at 100° C., A to C were good, and A was the most excellent.
[0270] (iii) 100°C lamination wrinkle evaluation
[0271] Ten A4-sized laminated samples of the copper foil substrate and the biaxially oriented polyester sample laminated at a lamination roll temperature of 100° C. used in the above item (ii) were visually checked for the presence or absence of wrinkles of 1 cm or more in length generated during lamination and evaluated as follows.
[0272] A: Laminated wrinkles occurred in less than 1 of 10 laminated samples.
[0273] B: Laminated wrinkles occurred in 2 or more and 3 or less of the 10 laminated samples.
[0274] C: Laminated wrinkles occurred in 4 or more and 6 or less of 10 laminated samples.
[0275] D: Laminated wrinkles occurred in 7 or more laminated samples out of 10 sheets.
[0276] As for the evaluation of 100°C lamination wrinkles, A to C were good, and A was the most excellent.
[0277] (iv) Lamination void evaluation at 120°C
[0278] Ten A4-sized laminated samples of the copper foil substrate and the biaxially oriented polyester sample laminated at a lamination roll temperature of 120°C obtained in the previous items (i) a. to b. were visually confirmed to confirm the presence or absence of floating between the laminated layer and the biaxially stretched polyester sample layer. The number of samples with floating (lamination voids) with a major diameter of the void exceeding 1 mm was evaluated as follows.
[0279] A: Lamination voids occurred in less than 1 sheet among 10 sheets of laminated samples.
[0280] B: Among the 10 laminated samples, lamination voids occurred in 2 or more and 3 or less sheets.
[0281] C: Among the 10 laminated samples, lamination voids occurred in 4 or more and 6 or less sheets.
[0282] D: Lamination voids occurred in 7 or more sheets among 10 sheets of laminated samples.
[0283] As for the 120°C lamination void evaluation, A to C were good, and A was the most excellent.
[0284] (v) 120°C Lamination Wrinkle Evaluation
[0285] For 10 A4-sized laminated samples of the copper foil substrate and the biaxially oriented polyester sample laminated at a lamination roll temperature of 120°C used in the preceding item (iv), the presence or absence of wrinkles (lamination wrinkles) with a height of more than 2 mm and a length of more than 1 cm generated during lamination were visually confirmed and evaluated as follows.
[0286] A: Laminated wrinkles occurred in less than 1 of 10 laminated samples.
[0287] B: Laminated wrinkles occurred in 2 or more and 3 or less of the 10 laminated samples.
[0288] C: Laminated wrinkles occurred in 4 or more and 6 or less of 10 laminated samples.
[0289] D: Laminated wrinkles occurred in 7 or more laminated samples out of 10 sheets.
[0290] As for the 120°C lamination wrinkle evaluation, A to C were good, and A was the most excellent.
[0291] C. Fine wiring resist evaluation
[0292] (i) Fine wiring formation using projection exposure
[0293] Regarding the 10 samples obtained in the above item (i) of B and laminated at a laminating roll temperature of 120°C, a photomask patterned with chromium metal (L / S (μm) (Line and Space) = 5μm / 5μm 30 lines of the resist wiring pattern) was arranged on the opposite side of the biaxially oriented polyester film to the surface on which the resist layer was provided (the surface of the P1 layer), and projection exposure was carried out from the photomask (from the surface side of the P1 layer of the biaxially oriented polyester film of the present invention) using an i-ray (ultraviolet rays having a peak at a wavelength of 365nm) stepper equipped with a projection lens.
[0294] Then, after the polyester film was peeled off from the photosensitive resin layer, the photosensitive resin layer was added to a container with developer N-A5 and developed for about 1 minute. Then, it was taken out from the developer and washed with water for about 1 minute. The state of L / S (μm) (line and space) = 5μm / 5μm 30 lines of the resist wiring pattern produced after development was observed using a scanning electron microscope (SEM) at a magnification of about 800 to 3000.
[0295] (ii) Fine wiring area defect evaluation
[0296] Regarding the 10 fine wiring resist wiring forming samples obtained in the previous item (i), regarding the 30 wiring pattern areas formed using each sample, the number of pieces in which regional defects with an equivalent circle diameter of more than 100 μm, which caused wiring shape defects spanning multiple wirings, was confirmed, and evaluation was performed based on the number of pieces as described below.
[0297] A: There is less than 1 sample with regional defects
[0298] B: The number of samples having regional defects is 2 or more and 3 or less.
[0299] C: The number of samples having regional defects is 4 or more and 6 or less.
[0300] D: The number of samples having regional defects is 7 or more.
[0301] (iii) Evaluation of fine wiring resist shape (5 μm width evaluation)
[0302] Regarding the 10 fine wiring resist wiring forming samples used for evaluation in the previous item (ii), the number of wiring patterns with recessed portions having a straight line shape deformed by more than 0.5 μm in the long side portions of the upper surfaces of the 30 wiring patterns formed in each sample was confirmed in each of the 10 samples, and their average value was used to evaluate the fine wiring resist shape (5 μm width) of the film as described below.
[0303] S: The number of missing items is less than 1 on average
[0304] A: The number of missing items is more than 2 and less than 3 on average.
[0305] B: The number of lines with deletions is 4 or more and 7 or less on average.
[0306] C: The number of lines with deletions is 8 or more and 10 or less on average.
[0307] D: The number of missing lines is 11 or more on average.
[0308] As for the fine wiring resist shape evaluation (5 μm width), A to C were good, and A was the most excellent.
[0309] (iv) Micro-wiring pinhole defects
[0310] Regarding the 10 fine wiring resist wiring formation samples used for evaluation in the previous item (ii), regarding the 30 resist wiring patterns formed in each sample, the number of wiring patterns with missing portions of 1.5 μm or more was confirmed, and their average value was used to evaluate the fine wiring pinhole defects of the film as described below.
[0311] A: The number of pinhole defects is 0 on average
[0312] B: The number of pinhole defects is 1 or more and 5 or less on average.
[0313] C: The number of pinhole defects is 6 or more and 10 or less on average.
[0314] D: The number of lines with pinhole defects exceeds 10 on average.
[0315] As for the fine wiring pinhole defect evaluation, A to C were good, and A was the most excellent.
[0316] (v) Evaluation of fine wiring resist shape (8 μm width evaluation)
[0317] As in the previous item (i), a photomask patterned with chromium metal was used (L / S (μm) (Line and Space) of the resist wiring pattern = 8μm / 8μm, 30 lines), and 10 samples were obtained in which the L / S (μm) (Line and Space) of the resist wiring pattern produced after development was 8μm / 8μm, and 30 wiring lines were formed.
[0318] Regarding 10 samples of fine wiring resist wiring formation, the number of wiring patterns with recessed portions having a straight line shape deformed by more than 0.8 μm in the long side portions of the upper surfaces of the 30 wiring patterns formed in each sample was confirmed in each of the 10 samples, and their average value was used to evaluate the fine wiring resist shape (8 μm width) of the film as described below.
[0319] S: The number of missing items is less than 1 on average
[0320] A: The number of missing items is more than 2 and less than 3 on average.
[0321] B: The number of lines with deletions is 4 or more and 7 or less on average.
[0322] C: The number of lines with deletions is 8 or more and 10 or less on average.
[0323] D: The number of missing lines is 11 or more on average.
[0324] As for the evaluation of fine wiring resist shape (8 μm width), A to C were good, and A was the most excellent.
[0325] (vi) Evaluation of fine wiring resist shape (3 μm width evaluation)
[0326] As in the previous item (i), a photomask patterned with chromium metal was used (L / S (μm) (Line and Space) of the resist wiring pattern = 3μm / 3μm, 30 lines), and 10 samples were obtained in which the L / S (μm) (Line and Space) of the resist wiring pattern produced after development was 3μm / 3μm and 30 wiring lines were formed.
[0327] Regarding 10 samples of fine wiring resist wiring formation, the number of wiring patterns with recessed portions having a straight line shape deformed by more than 0.3 μm in the long side portions of the upper surfaces of the 30 wiring patterns formed in each sample was confirmed in each of the 10 samples, and their average value was used to evaluate the fine wiring resist shape (3 μm width) of the film as described below.
[0328] S: The number of missing items is less than 1 on average
[0329] A: The number of missing items is more than 2 and less than 3 on average.
[0330] B: The number of lines with deletions is 4 or more and 7 or less on average.
[0331] C: The number of lines with deletions is 8 or more and 10 or less on average.
[0332] D: The number of missing lines is 11 or more on average.
[0333] As for the evaluation of fine wiring resist shape (3 μm width), A to C were good, and A was the most excellent.
[0334] Example
[0335] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not necessarily limited to these Examples.
[0336] [Production of PET-1] A melt-polymerized PET substantially free of particles was obtained by polymerizing terephthalic acid and ethylene glycol using antimony trioxide as a catalyst by a conventional method. The obtained melt-polymerized PET had a glass transition temperature of 81°C, a melting point of 255°C, and an intrinsic viscosity of 0.50.
[0337] Then, the obtained polyester pellets were dried at 160°C for 6 hours to crystallize, and then solid phase polymerization was performed at 220°C and a vacuum degree of 0.3 Torr for 8 hours to obtain solid phase polymerized PET (PET-1). The obtained solid phase polymerized PET had a glass transition temperature of 81°C, a melting point of 255°C, and an intrinsic viscosity of 0.61.
[0338] [Production of PET-2] The same operation as the previous item [Production of PET-1] was carried out to obtain solid phase polymerization PET resin particles (PET-2) with a glass transition temperature of 81°C, a melting point of 255°C, and an intrinsic viscosity of 0.56.
[0339] [Manufacture of MB-A] During the polymerization of PET-1 in the above item, alumina particles (alumina-1) having an average primary particle size of 20 nm dispersed in ethylene glycol were added in such a manner that the addition amount relative to PET was 2% by mass, and then filtered with a filter having a high-precision capture rate of 95% or more of foreign matter of 5 μm or more, to obtain a master particle MB-A. The obtained master particle MB-A had a glass transition temperature of 80°C, a melting point of 255°C, and an intrinsic viscosity of 0.59.
[0340] [Manufacturing of MB-B to G] The same method as in the previous item [Manufacturing of MB-A] was used. During the polymerization of PET-1 or PET-2, the particles described in Table 1 were added in an amount relative to PET as described in Table 1, dispersed in ethylene glycol, to obtain master particles MB-B to G. The properties of the master particles are as described in Table 1.
[0341] [Table 1]
[0342]
[0343] [Coating composition A] [Resin (A)]
[0344] ·Acrylic resin (a-1)
[0345] An acrylic acid-based monomer copolymer "Nikazol" (registered trademark) RX7013ED (solid content concentration: 35%, solvent: water) manufactured by Nippon Kaido Industries was used.
[0346] ·Acrylic resin (a-2)
[0347] In a stainless steel reaction container, 75 parts by mass of methyl methacrylate (a), 20 parts by mass of hydroxyethyl methacrylate (b), and urethane acrylate oligomer (manufactured by Negami Industries, Ltd., Artlexin (registered trademark) UN-3320HA, the number of acryloyl groups being 6) (c) were added in a ratio of parts by mass, and 2 parts by mass of sodium dodecylbenzenesulfonate as an emulsifier was added relative to a total of 100 parts by mass of the above (a) to (c), and stirred to prepare a mixed solution 1. Next, a reaction apparatus equipped with a stirrer, a reflux cooling tube, a thermometer, and a dropping funnel was prepared. 60 parts by weight of the above mixed solution 1, 200 parts by weight of isopropyl alcohol, and 5 parts by weight of potassium persulfate as a polymerization initiator were added to the reaction apparatus, and heated to 60°C to prepare a mixed solution 2. The mixed solution 2 was kept in a heated state at 60°C for 20 minutes. Next, a mixed solution 3 consisting of 40 parts by weight of the mixed solution 1, 50 parts by weight of isopropyl alcohol and 5 parts by weight of potassium persulfate was prepared. Next, the mixed solution 3 was added dropwise to the mixed solution 2 over 2 hours using a dropping funnel to prepare a mixed solution 4. Then, the mixed solution 4 was kept heated to 60°C for 2 hours. After the obtained mixed solution 4 was cooled to below 50°C, it was transferred to a container equipped with a stirrer and a decompression device. 60 parts by weight of ammonia water with a concentration of 25% by weight and 900 parts by weight of pure water were added thereto, and the isopropyl alcohol and unreacted monomers were recovered under reduced pressure while being heated to 60°C, and an acrylic resin (a-2) dispersed in pure water was obtained and used.
[0348] ·Acrylic resin (a-3)
[0349] The method described for the acrylic resin (a-2) was used to use an aqueous dispersion (average particle size: 110 nm, solid content concentration 40%) of a water-dispersible acrylic copolymer (glass transition temperature 80° C.) composed of methyl methacrylate / ethyl ethacrylate / acrylic acid / N-hydroxymethyl acrylamide.
[0350] [Crosslinking agent (B)]
[0351] ·Hydroxymethylated melamine resin (b-1)
[0352] "Nikalak" (registered trademark) MW12LF (solid content concentration: 70 mass %, solvent: water) manufactured by Sanwa Chemical Co., Ltd. was used.
[0353] [Particle composition (C)]
[0354] Particles (c-1)
[0355] A water dispersion of silica "CATALOD" (registered trademark) SI-80P (solid content concentration: 10% by mass, solvent: water) having an average primary particle size of 80 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd., was used.
[0356] The acrylic resin (a-1), methylolated melamine resin (b-1), particles (c-1), and water as a solvent were mixed in the ratios shown in Table 2 to obtain a mixed solution having a solid content concentration of 3%. To 100 parts of the mixed solution, 0.1 parts of surfactant "Olfin" (registered trademark) EXP4051F (solid content concentration 70 mass %, solvent: water) manufactured by Shin-Etsu Chemical Co., Ltd. was added in liquid ratio to obtain [Coating composition A].
[0357] [Coating compositions B, C]
[0358] [Coating composition B] and [Coating composition C] were obtained in the same manner as [Coating composition A] except that the acrylic resin used was changed as shown in Table 2 and mixed in the ratio described in Table 2.
[0359] [Table 2]
[0360]
[0361] (Example 1)
[0362] After PET resin pellets PET-1, PET-2, and masterbatch MB-A to C were dried under reduced pressure at 180°C for 2.5 hours, they were mixed in amounts corresponding to the P1 layer, P2 layer, and P3 layer as shown in Table 3, respectively, and supplied to three extruders for melt extrusion. After filtering with a filter, the materials were combined in a stacked manner to form a three-layer structure (P1 layer / P3 layer / P2 layer structure) using a feed block, and then wound on a cooling casting roll maintained at 42°C using an electrostatic casting method through a T-die, and cooled and solidified to obtain an unstretched film. Here, the filters of the P1 layer and the P2 layer were filtered using a high-precision filter that captured more than 95% of foreign matter of 5μm or more, and the filter of the P3 layer was filtered using a high-precision filter that captured more than 95% of foreign matter of 2μm or more, and melt extruded.
[0363] The unstretched film was introduced between the opposing electrodes and the grounded roll, and nitrogen was introduced into the device. When the treatment intensity (E value) became 280 W·min / m 2 Under the conditions of atmospheric pressure glow discharge plasma treatment was carried out on the surface of the P2 layer.
[0364] After the treated unstretched film was passed through a destaticizing roller whose roller temperature was set to 25°C, it was subjected to a sequential biaxial stretching machine under the conditions described in Table 4. First, in the longitudinal direction, it was guided to a stretching roller group heated to 60°C to 100°C, stretched by a total of 3.8 times by a stretching operation, and then guided to a tenter and stretched by 4.3 times in the width direction. Heat treatment was performed at 230°C at a fixed length and relaxation treatment was performed in the width direction as described in Table 4, thereby obtaining a biaxially oriented polyester film with a thickness of 16 μm.
[0365] [Table 3]
[0366]
[0367] [Table 4-1]
[0368]
[0369] [Table 4-2]
[0370] Table 4-2
[0371]
[0372] [Table 4-3]
[0373]
[0374] [Table 4-4]
[0375] Table 4-4
[0376]
[0377] The structure and film properties of the obtained biaxially oriented polyester film are shown in Tables 5 and 6.
[0378] [Table 5]
[0379] Table 5
[0380]
[0381] [Table 6]
[0382]
[0383] As shown in Table 7, the film has good production suitability and application suitability, and is excellent in film productivity, high-temperature lamination processing suitability, and dry film resist suitability.
[0384] [Table 7]
[0385]
[0386] (Examples 2 to 20)
[0387] In Examples 2 to 5, biaxially oriented polyester films were produced under the film-forming conditions described in Tables 2 to 4. Here, in Example 12, after P2 layer and P3 layer were laminated after melt extrusion, P1 layer was provided on the opposite surface of P3 layer in the film after longitudinal stretching to the surface where P2 layer was provided by an in-line coating method using coating composition A described in Table 2 so that the coating thickness after drying was as described in Table 4, thereby obtaining a biaxially oriented polyester film having a three-layer structure (P1 layer / P3 layer / P2 layer structure).
[0388] In Examples 19 and 20, except that the coating composition was changed to coating composition B and coating composition C, respectively, as described in Table 3, the same operation was carried out as in Example 12, and a biaxially oriented polyester film with a three-layer structure (P1 layer / P3 layer / P2 layer structure) in which the P1 layer was arranged in a manner such that the coating film thickness after drying became as described in Table 4 was obtained by an online coating method.
[0389] The structure and film properties of the obtained biaxially oriented polyester film are shown in Tables 5 and 6.
[0390] As shown in Table 7, the production suitability and application suitability of the film are equal to or inferior to those of Example 1 in terms of film productivity, high temperature lamination process suitability, and dry film resist suitability. However, the film is a practically acceptable film.
[0391] (Comparative Examples 1 to 5)
[0392] In Comparative Examples 1 to 5, biaxially oriented polyester films were produced under the film-forming conditions described in Tables 2 to 4.
[0393] The structure and film properties of the obtained biaxially oriented polyester film are shown in Tables 5 and 6.
[0394] As shown in Table 7, the production suitability and application suitability of the film are significantly inferior to those of Example 1 in terms of film productivity, high temperature lamination process suitability, and dry film resist suitability.
[0395] Industrial Availability
[0396] The biaxially oriented polyester film of the present invention has excellent processing adaptability in a high-temperature lamination process in a dry film resist film by controlling the thermal dimensional change rate of the film in a specific temperature range, and has both productivity and good optical properties by controlling the particle size and surface shape contained in both side surface layers. Therefore, it is suitable for use as a support film for a dry film resist for fine wiring.
[0397] Explanation of symbols
[0398] 1. Layer having a surface with protrusions (P2 layer)
[0399] 2. Surface with protrusions (P2 layer surface)
[0400] 3. Zero plane (average plane; height 0nm) in scanning white interference microscope measurement
[0401] 4. 10 nm high line (R 10nm )
[0402] 5. Protrusions on the surface of the P2 layer
[0403] 6. Moving surface layer containing particles (P1 layer)
[0404] 7. Moving surface (P1 layer surface)
[0405] 8. Biaxially oriented polyester film with 2-layer structure (P1 layer / P2 layer)
[0406] 9. Middle layer (P3 layer)
[0407] 10. Biaxially oriented polyester film with 3-layer structure (P1 layer / P3 layer / P2 layer)
[0408] 11. Middle layer (P4 layer)
[0409] 12. A biaxially oriented polyester film having a 4-layer structure (P1 layer / P4 layer / P3 layer / P2 layer).
Claims
1. A biaxially oriented polyester film for a dry film resist support, wherein the film dimensional change rate when the film temperature is raised from 90°C to 130°C is denoted as ΔL 90-130℃ In the case of ΔL in at least one direction of the width direction, i.e., the TD direction, and the length direction, i.e., the MD direction 90-130℃ is greater than -50 and less than 150, the total film thickness T is greater than 11 and less than 50, the ΔL 90-130℃ The unit of is ppm / °C, and the unit of T is μm.
2. The biaxially oriented polyester film for a dry film resist support according to claim 1, wherein the film dimensional change rate when the film temperature is raised from 90°C to 130°C is denoted by ΔL 90-130℃ In the case of ΔL in at least one direction of the width direction, i.e., the TD direction, and the length direction, i.e., the MD direction 90-130℃ is 20 or more and 150 or less, the total film thickness T is 11 or more and 50 or less, the ΔL 90-130℃ The unit of is ppm / °C, and the unit of T is μm.
3. The biaxially oriented polyester film for a dry film resist support according to claim 1 or 2, wherein the ΔL 90-130℃ The dimensional change rate ΔL when the film temperature is increased from 110°C to 130°C in the direction of -50° to 150° 110-130℃ is 0 or more, the ΔL 90-130℃ and the ΔL 110-130℃ The unit is ppm / ℃.
4. The biaxially oriented polyester film for a dry film resist support according to claim 1 or 2, wherein relative to the ΔL 90-130℃ The dimensional change rate ΔL when the temperature is increased from 90°C to 130°C in the direction of -50° or more and 150° or less, which is the perpendicular direction in the plane 90-130℃ is greater than -200 and less than 0, the ΔL 90-130℃ The unit is ppm / ℃.
5. The biaxially oriented polyester film for a dry film resist support according to claim 1 or 2, wherein the ΔL 90-130℃ The dimensional change rate ΔL when the film temperature is increased from 90°C to 110°C in the direction of -50° to 150° 90-110℃ is 0 or more, the ΔL 90-130℃ and the ΔL 90-110℃ The unit is ppm / ℃. 6 . The biaxially oriented polyester film for a dry film resist support according to claim 1 , wherein the root mean square roughness Sq of at least one surface is 0.8 or more and less than 3.0, wherein the unit of Sq is nm. 7 . The biaxially oriented polyester film for a dry film resist support according to claim 1 , comprising a P1 layer as at least one outermost layer, wherein the P1 layer is a layer containing particles having an average primary particle size of 70 nm to 200 nm.
8. The polyester film for a dry film resist support according to claim 7, wherein the thickness of the P1 layer is set to T P1 In case of T P1 is greater than or equal to 0.03 and less than or equal to 0.35, the T P1 The unit is μm.
9. The biaxially oriented polyester film for a dry film resist support according to claim 7, wherein the root mean square roughness of the surface of the P1 layer is defined as Sq P1 Case Sq P1 is greater than 0.8 and less than 3.0, the Sq P1 The unit is nm.
10. The biaxially oriented polyester film for a dry film resist support according to claim 7, wherein the outermost layer P2 layer on the opposite side to the P1 layer satisfies the following (1) and (2): (1) does not contain particles having an average primary particle size of 200 nm or more, (2) The surface has protrusions, and the number of protrusions with a height of 10 nm or more is N. 10nm In the case of N 10nm is greater than 600 and less than 12000, the N 10nm The unit is piece / mm 2 . 11 . The biaxially oriented polyester film for a dry film resist support according to claim 10 , further comprising a P3 layer between the P1 layer and the P2 layer, wherein the P3 layer has a lower particle concentration than the P1 layer or contains no particles.
12. The biaxially oriented polyester film for a dry film resist support according to claim 7, wherein the number of coarse particles having a major diameter of 2.0 μm or more existing in a region 3 μm away from the P1 layer in the film thickness direction observed by an optical microscope is defined as N. P1 In the case of N P1 is less than 20, the N P1 The unit is piece / 8.25mm 2 .
Citation Information
Patent Citations
Thermal transfer ribbon
JP1998024665A
Biaxially oriented polyester film and laminates thereof with copper
JP2015178623A
Polyester film for thermal transfer ink ribbon
JP2021054069A
Polyester film roll for support of ceramic green sheet
JP2021160240A